Outsourcing, unemployment and welfare policy - Keuschnigg, Christian; Ribi, Evelyn (Munich, 2008)
"The paper investigates the consequences of outsourcing of labor intensive activities to low-wage economies. This trend challenges the two basic functions of the welfare state, redistribution and social insurance when private unemployment insurance markets are missing. The main results are: (i) outsourcing raises unemployment and labor income risk of unskilled workers; (ii) it increases inequality among high- and low-income groups; and (iii) the gains from outsourcing can be made Pareto improving by using a redistributive linear income tax if redistribution is initially not too large. We finally derive the welfare optimal redistribution and unemployment insurance policies."